Against youth violence : a social harm perspective - Billingham, Luke; Irwin-Rogers, Keir (Studies in social harm., 2022)
Youth violence dominates headlines and politicians' attention and many organisations invest considerable resources in an attempt to reduce it. This book examines how inequality and social harms drive such violence and highlights key future goals for policymakers, researchers and practitioners.